Calculus of directional subdifferentials and coderivatives in Banach spaces - Long, Pujun; Wang, Bingwu; Yang, Xinmin (Positivity : an international journal devoted to the theory and applications of positivity in analysis, 2017)
In this work we study the directional versions of Mordukhovich normal cones to nonsmooth sets, coderivatives of set-valued mappings, and subdifferentials of extended-real-valued functions in the framework of general Banach spaces. We establish some characterizations and basic properties of these constructions, and then develop calculus including sum rules and chain rules involving smooth functions. As an application, we also explore the upper estimates of the directional Mordukhovich subdifferentials and singular subdifferentials of marginal functions.